Development of Interdisciplinary Higher-Order Thinking Teaching Module: Insights from Delphi Consensus - Zhenduo, Ding; Othman, Mohd Syaubari bin; Hosshan, Hasrul (Journal of Ecohumanism, 2024)
The aim of this study was to design and develop an interdisciplinary Higher Order Thinking Skills (HOTS) teaching module for first year university students. In order to derive appropriate elements of the teaching module in terms of interdisciplinary knowledge and HOTS, 18 experts were recruited to participate in the design development and module review. A total of 3 rounds of the Delphi method were implemented to derive the module elements, and we used interquartile range (IQR) and Z-score to determine the degree of consensus of the panellists, which resulted in 39 consensus module elements out of 41 items, which were consolidated into 7 constructs, and these were applied to the development of the teaching module.